The Impact of Workload, Organizational Culture, and Motivation for Organizational Citizenship Behavior that is Mediated by Loyalty - Herawati, Jajuk; Soni Kurniawan, Ignatius; Azhari, Linda (Universitas Muhammadiyah Yogyakarta, 2021)
Instilling an attitude to employees for having the willingness to give their best performance without taking into consideration of feedback obtained is necessarily needed and certainly profitable for the company. This attitude denotes a form of Organizational Citizenship Behavior (OCB). This study examines how big the impact of workload, organizational culture, and motivation on OCB with loyalty mediation. The participants of this study are the employees of PT Bummy Harapan Umat Yogyakarta with 50 people as the sample. The testing was done by using multiple regression analysis and the Sobel test. The result of this study showed that loyalty is able to mediate the impact of workload, organizational culture, and motivation of OCB.